1H NMR structural signatures of source and atmospheric organic aerosols in India. (August 2022) - Yadav, Suman; Sam, Avik Kumar; Venkataraman, Chandra; Kumar, Ashutosh; Phuleria, Harish C.
Abstract: Organic aerosols (OA) play significant roles in several atmospheric processes and adversely impact human health. This study examines the key structural units present in water- and methanol-soluble organic carbon (WSOC, MSOC) fraction of OA from emission sources (traffic and biomass cooking) and an urban background location in India. Proton nuclear magnetic resonance ( 1 H NMR) spectroscopy was employed to assess the distribution of non-exchangeable proton structural groups of the OAs. Organic carbon, elemental carbon, black carbon, and water-soluble organic carbon (WSOC) analyses were also conducted. The 1 H NMR analysis corroborated that the WSOC and MSOC fractions hold similar 1 H structural groups; however, they differ in their relative distribution and absolute concentrations across the ambient locations and source emissions. The relative contribution of the proton structural groups to OA was in the order C-H > H–C–C=> H–C–O > Ar–H. The aliphatic concentration was lower in the morning tunnel entry aerosols when compared to other tunnel aerosols, whereas the unsaturated structures (H–C–C= ) were present in all the tunnel aerosols within a range of 47.2–62.3 μmol/m 3 . The aromatic groups were the maximum in the firewood aerosols, about 1.4 and 3.7 times higher than the crop residue and the mixed fuel aerosols, respectively. The total functional groups, i.e., the sum of all the observed groups, significantly correlated with C–H (r = 0.96) and WSOC (r = 0.7), suggesting the higher contribution of aliphatic groups in the WSOC fraction. WSOC examined in this study fits well in the established 1 H NMR source identification fingerprints of urban aerosols. However, biomass cooking aerosols do not fit the established biomass burning organic aerosols (BBOAs) boundaries, exhibiting a smaller relative contribution of carbon-oxygen double bonds and a less oxidised character than open-field burning. Our results provide essential insights into the nature of urban atmospheric, near-traffic and biomass cooking OAs in India. Graphical abstract: Image 1 Highlights: Aerosols of traffic exhaust origin show more hydrophobic nature functional groups. Ar–H largely primary in origin and correlates positively with EC, WSOC and H–C at urban sites. WSOC fraction fits the established 1 H NMR source apportionment regions of urban aerosols. Biomass cooking aerosols depict distinct character and with new source boundaries.